Job satisfaction moderates the effect of competence and training on employee performance, a study on SMEs members of the Intako in Cooperative Sidoarjo Regency - Kusworo, Ahmad Dzulfikri Budi; Budiyanto, Budiyanto; Suwitho, Suwitho (Journal of Advances in Accounting, Economics, and Management, 2024)
This research is entitled "Job satisfaction moderates the effect of competence and training on employee performance", a study on SMEs members of the Intako in Cooperative Sidoarjo Regency. The purpose of this study is First, to test and analyze the effect of competence on the performance of employees of SMEs members of the Intako Cooperative in Sidoarjo Regency, to test and analyze the effect of training on the performance of employees of SMEs members of the Intako Cooperative in Sidoarjo Regency. Second, to test and analyze job satisfaction, moderating the effect of competence on the performance of SME employees who are members of the Intako Cooperative in Sidoarjo Regency. Third, to test and analyze job satisfaction moderating the effect of training on the performance of SME employees who are members of the Intako Cooperative in Sidoarjo Regency. The contributions in this study are: First, the contribution of theories, namely the results of this research is expected to provide a deep picture and understanding of the performance of SME employees who are members of the Intako Cooperative in Sidoarjo Regency. As well as references for similar studies in the future Second, the practical contribution of the results of this study is expected to be a reference for SMEs members of the Intako Cooperative to improve factors that affect employee performance. Third, policy contribution, namely the results of this research, is expected to be useful and used as input or evaluation in implementing government programs, especially in terms of community empowerment / SMEs carried out by the Office of Cooperatives and MSMEs, Industry, Trade, and Energy of Mineral Resources in Sidoarjo Regency. The data analysis technique used in this study, researchers used moderation analysis with data processing using the SmartPLS program version 3.0 starting from model measurement (outer model), model structure (inner model) and hypothesis testing. The results of testing the hypothesis of the model show that: First, competence has a significant effect, on employee performance, which means that the competencies possessed by employees are very good so that they have a meaningful influence on improving employee performance, so it can be said that the more competence increases, employee performance also increases. Second, training has a significant effect on employee performance, which means that the training provided by employees is good and has a meaningful influence on improving employee performance, so it can be said that the more training increases, of course employee performance increases. Third, job satisfaction is able to moderate the effect of competence on employee performance variables. Four, job satisfaction is able to moderate training on employee performance.